PDC (Polycrystalline Diamond Compact) doped liquid metal composite material and preparation method and application thereof

By doping metal oxide @ gallium-based liquid metal composite material into the ceramic precursor, the problems of poor dielectric regulation performance and insufficient electromagnetic wave absorption performance of gallium-based liquid metal in the ceramic precursor are solved, and high dielectricity is achieved The regulation and electromagnetic wave absorption performance are improved, and the photocuring performance of ceramic precursors is maintained, providing an effective electromagnetic protection solution.

CN119216572APending Publication Date: 2024-12-31SDIC CERAMIC MATRIX COMPOSITES RES INST (XIAN) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411115208.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-14
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

In traditional methods, gallium-based liquid metals have poor dielectric regulation performance and insufficient electromagnetic wave absorption performance when doping ceramic precursors, and affect the photocuring performance of ceramic precursors. It is difficult to prepare a composite of high dielectric regulation performance and high electromagnetic wave absorption performance. Material.

Method used

By mixing gallium-based liquid metal with metal oxide solution, a metal oxide@gadopedite liquid metal composite material is prepared and doped into a ceramic precursor. After curing and high-temperature pyrolysis, a core-shell structure composite is formed by forming a composite of the core-shell structure after curing and high-temperature pyrolysis. Material.

Benefits of technology

It achieves better dielectric control and electromagnetic wave absorption performance than pure gallium-based liquid metal, improves the dielectric control and electromagnetic wave absorption performance of composite materials, and does not affect the photocuring performance of ceramic precursors, providing effective electromagnetic Protection plan.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119216572A_ABST
    Figure CN119216572A_ABST
Patent Text Reader

Abstract

The invention discloses a PDC (Polycrystalline Diamond Compact) doped liquid metal composite material as well as a preparation method and application thereof, and belongs to the technical field of wave-absorbing composite materials. The preparation method comprises the following steps: (1) mixing gallium-based liquid metal and a metal oxide solution, and washing to obtain a metal oxide and gallium-based liquid metal composite material; and (2) dissolving the metal oxide and gallium-based liquid metal composite material obtained in the step (1) in a solvent, adding a ceramic precursor, uniformly mixing, removing the solvent, and carrying out curing and high-temperature pyrolysis to obtain the metal oxide and gallium-based liquid metal composite material. The metal oxide and gallium-based liquid metal composite material with the core-shell structure is obtained, the dielectric regulation and control capacity and the electromagnetic wave absorption performance better than those of pure liquid metal are achieved, and the dielectric regulation and control performance and the electromagnetic wave absorption performance of PDC can be greatly regulated and controlled by doping the metal oxide and gallium-based liquid metal composite material into PDC for composite material preparation; meanwhile, the original performance, especially the photocuring performance of the ceramic precursor, is not influenced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of wave-absorbing composite materials, and in particular to a PDC-doped liquid metal composite material and a preparation method and application thereof. Background Art

[0002] With the rapid development of wireless communications, various electronic and electrical equipment have also quickly entered people's lives. Society has become more and more intelligent, greatly improving the quality of human life. However, problems such as electromagnetic radiation and electromagnetic interference have become more and more serious, so advanced materials for electromagnetic protection have become a research hotspot. The existence of electromagnetic interference and electromagnetic radiation will not only cause instrument failure and information leakage, but also seriously affect human health. In order to achieve effective electromagnetic protection for the human body and electronic equipment and prevent increasingly serious electromagnetic pollution, people are in urgent need of materials that can effectively absorb electromagnetic waves and reduce secondary pollution of electromagnetic waves.

[0003] Polymer-derived ceramics (PDC) are a type of ceramic material obtained by pyrolysis of ceramic precursors (usually silicon-based polymers). By designing and regulating the configuration of polymer precursors, PDC can achieve many adjustable properties, such as high temperature resistance, high stability, and adjustable electromagnetic parameters. Studies have shown that composite materials prepared by co-pyrolysis of ceramic precursors with other materials can achieve more effective regulation of the properties of composite materials, and gallium-based liquid metals have unique electrochemical and mechanical properties, which undoubtedly shows great potential in doping PDC.

[0004] However, in the traditional method, the use of pure gallium-based liquid metal when doped with PDC will have problems such as poor dielectric control performance, insufficient electromagnetic wave absorption performance of the composite material, and will also affect the photocuring performance of the UV-curable ceramic precursor itself. It is not conducive to the preparation of composite materials with high dielectric control performance and high electromagnetic wave absorption performance, and will also affect the photocuring 3D printing performance of the ceramic precursor. Summary of the invention

[0005] In order to solve the above technical problems, the purpose of the present invention is to provide a PDC-doped liquid metal composite material and its preparation method and application, so as to solve the problems of poor dielectric control performance, insufficient electromagnetic wave absorption performance, and affecting the photocuring performance of the ceramic precursor itself when the existing gallium-based liquid metal is doped with PDC.

[0006] The technical solution of the present invention to solve the above technical problems is as follows:

[0007] A method for preparing a PDC-doped liquid metal composite material comprises the following steps:

[0008] (1) mixing a gallium-based liquid metal and a metal oxide solution, washing, and obtaining a metal oxide@gallium-based liquid metal composite material;

[0009] (2) dissolving the metal oxide@gallium-based liquid metal composite material obtained in step (1) in a solvent, adding a ceramic precursor and mixing evenly, removing the solvent, and curing and high-temperature pyrolysis to obtain a composite material.

[0010] The beneficial effects of the present invention are as follows: the present invention prepares metal oxide @ gallium-based liquid metal materials on the basis of gallium-based liquid metal, the preparation method is simple, and batch preparation is possible; the obtained material has a core-shell structure, and doping into a ceramic precursor will not affect its photocuring efficiency; at the same time, dielectric regulation of the composite material can be achieved, and the electromagnetic wave absorption performance of the composite material can be greatly improved.

[0011] Furthermore, in step (1), the mass volume ratio of the gallium-based liquid metal to the metal oxide solution is 0.1-0.5 g: 20-100 mL; the gallium-based liquid metal is EGa1n, Ga or Galinstan, and the metal oxide solution is KMnO4 solution.

[0012] Furthermore, the concentration of the metal oxide solution is 2-10 mmol / L.

[0013] Furthermore, the mixing conditions in step (1) are: ultrasound at 1200-1600W for 20-40min in an ice bath.

[0014] Preferably, the mixing condition in step (1) is: ultrasound at 1400W for 30 min in an ice bath.

[0015] Furthermore, in step (1), washing is performed by washing with water and tetrahydrofuran respectively.

[0016] Furthermore, in step (2), the mass ratio of the metal oxide@gallium-based liquid metal composite material to the ceramic precursor is: 0.1%-2%:1; and the solvent is tetrahydrofuran.

[0017] Furthermore, the method of removing the solvent in step (2) is rotary evaporation.

[0018] Furthermore, the curing condition in step (2) is a light irradiation intensity of 10-20 mW / cm 2 , time is 1-30s.

[0019] Furthermore, the conditions for high temperature pyrolysis in step (2) are: in a rare gas atmosphere, first heat to 150-200°C, keep warm for 1-2h, then heat to 300-400°C, keep warm for 2-3h, and finally heat to 900-1200°C, keep warm for 2-3h, and the heating rate is 1-2°C / min.

[0020] A PDC-doped liquid metal composite material is prepared by adopting the above preparation method.

[0021] Application of the above PDC-doped liquid metal composite material in the preparation of wave absorbing materials.

[0022] The present invention has the following beneficial effects:

[0023] The present invention, based on liquid metal, utilizes the replacement reaction of highly oxidized metal salt to obtain a metal oxide@gallium-based liquid metal composite material with a core-shell structure, achieving better dielectric control ability and stronger electromagnetic wave absorption performance than pure liquid metal. Doping into a ceramic precursor for composite material preparation can greatly improve the dielectric control performance and electromagnetic wave absorption performance of PDC, while not affecting the original performance of the ceramic precursor, especially the photocuring performance, providing a feasible solution to electromagnetic radiation and electromagnetic pollution, and can protect human health and ensure the safe operation of electronic equipment. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is a SEM photo of the metal oxide@gallium-based liquid metal composite material in Experimental Example 1;

[0025] Figure 2 This is the energy spectrum photo of the metal oxide@gallium-based liquid metal composite material in Experimental Example 1;

[0026] Figure 3 The XRD spectrum of the metal oxide@gallium-based liquid metal composite material in Experimental Example 1;

[0027] Figure 4 The pictures of samples with different MnO2@EGaln doping amounts in Experimental Example 2 after curing for 6 seconds;

[0028] Figure 5 is the thickness of samples with different MnO2@EGaln doping amounts after curing for 6 seconds in Experimental Example 2;

[0029] Figure 6 This is a comparison diagram of samples with different MnO2@EGaln doping amounts before and after pyrolysis in Experimental Example 2;

[0030] Figure 7 This is the TEM element mapping image of the sample of Example 1 in Experimental Example 2 after 3D printing and curing at 1000°C pyrolysis;

[0031] Figure 8 This is the complex dielectric constant diagram of the sample of Example 1 in Experimental Example 3 after 3D printing and curing at 1000°C pyrolysis;

[0032] Fig. 9This is a reflection coefficient diagram of different thicknesses of the sample of Example 1 in Experimental Example 3 after 3D printing and curing at 1000°C pyrolysis;

[0033] Fig.10 This is the complex dielectric constant diagram of the sample of Example 7 in Experimental Example 3 after 3D printing and curing at 1000°C pyrolysis;

[0034] Fig.11 This is a reflection coefficient diagram of different thicknesses of the sample of Example 7 in Experimental Example 3 after 3D printing and curing at 1000°C pyrolysis;

[0035] Fig.12 This is the complex dielectric constant diagram of the sample of Example 1 in Experimental Example 3 after 3D printing and curing at 900°C pyrolysis;

[0036] Fig.13 This is a reflection coefficient diagram of different thicknesses of the sample of Example 1 in Experimental Example 3 after 3D printing, curing and pyrolysis at 900°C;

[0037] Fig.14 The complex dielectric constant diagram of the pure PDC sample obtained after 3D printing curing and 1000°C pyrolysis in Experimental Example 3;

[0038] Fig.15 This is a reflection coefficient diagram of different thicknesses of the pure PDC sample obtained after 3D printing, curing and pyrolysis at 1000°C in Experimental Example 3. DETAILED DESCRIPTION

[0039] The principles and features of the present invention are described below in conjunction with the accompanying drawings. The examples are only used to explain the present invention and are not used to limit the scope of the present invention. If specific conditions are not specified in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0040] Embodiment 1:

[0041] A method for preparing a PDC-doped liquid metal composite material comprises the following steps:

[0042] (1) 0.3 g EGaln and 50 mL 4 mmol / L KMnO4 were added to a cell disruptor, and the power of the cell disruptor was adjusted to 1400 W. The mixed solution was ultrasonicated for 30 min in an ice bath. After the ultrasonication, the mixed solution was washed with water and tetrahydrofuran for 3 times, respectively. When washing with water, the centrifuge speed was 2500 rpm for 3 min. When washing with tetrahydrofuran, the centrifuge speed was 1500 rpm for 3 min. MnO2@EGaln with a core-shell structure was obtained.

[0043] (2) The MnO2@EGaln obtained in step (1) is dissolved in tetrahydrofuran, and then doped with a ceramic precursor (a hyperbranched UV-curable ceramic precursor prepared by non-hydrolytic condensation reaction using alkoxysilane and boric acid as raw materials), wherein the doping amount of MnO2@EGaln is 0.5%. After uniform mixing, the tetrahydrofuran is removed by rotary evaporation, and the PDC-doped liquid metal composite material is obtained by curing and high-temperature pyrolysis; the curing condition is a light irradiation intensity of 15 mW / cm 2 The high temperature pyrolysis conditions are as follows: in an argon atmosphere, first heat to 180 °C, keep warm for 1.5 h, then heat to 350 °C, keep warm for 2.5 h, and finally heat to 1000 °C or 900 °C, keep warm for 2 h, and the heating rate is 1 °C / min.

[0044] Embodiment 2:

[0045] A method for preparing a PDC-doped liquid metal composite material comprises the following steps:

[0046] (1) 0.3 g Ga and 50 mL 4 mmol / L KMnO4 were added to a cell disruptor, and the power of the cell disruptor was adjusted to 1400 W. The mixed solution was ultrasonicated for 30 min in an ice bath. After the ultrasonication, it was washed with water and tetrahydrofuran for 3 times, respectively. When washing with water, the centrifuge speed was 2500 rpm for 3 min. When washing with tetrahydrofuran, the centrifuge speed was 1500 rpm for 3 min. MnO2@Ga with a core-shell structure was obtained.

[0047] (2) dissolving the MnO2@Ga obtained in step (1) in tetrahydrofuran, and then doping it with a ceramic precursor, wherein the MnO2@Ga doping amount is 0.5%, and after mixing evenly, removing the tetrahydrofuran by rotary evaporation, and obtaining a PDC-doped liquid metal composite material by curing and high-temperature pyrolysis; the curing condition is a light irradiation intensity of 15 mW / cm 2 The high temperature pyrolysis conditions are as follows: in an argon atmosphere, first heat to 180 °C, keep warm for 1.5 h, then heat to 350 °C, keep warm for 2.5 h, and finally heat to 1000 °C, keep warm for 2 h, and the heating rate is 1 °C / min.

[0048] Embodiment 3:

[0049] A method for preparing a PDC-doped liquid metal composite material comprises the following steps:

[0050] (1) 0.3 g EGaln and 50 mL 8 mmol / L KMnO4 were added to a cell disruptor, and the power of the cell disruptor was adjusted to 1400 W. The mixed solution was ultrasonicated for 30 min in an ice bath. After the ultrasonication, the mixed solution was washed with water and tetrahydrofuran for 3 times, respectively. When washing with water, the centrifuge speed was 2500 rpm for 3 min. When washing with tetrahydrofuran, the centrifuge speed was 1500 rpm for 3 min. MnO2@EGaln with a core-shell structure was obtained.

[0051] (2) The MnO2@EGaln obtained in step (1) is dissolved in tetrahydrofuran, and then doped with PDC, the MnO2@EGaln doping amount being 0.5%. After being evenly mixed, the tetrahydrofuran is removed by rotary evaporation, and the PDC-doped liquid metal composite material is obtained by curing and high-temperature pyrolysis; the curing condition is a light irradiation intensity of 15 mW / cm 2 The high temperature pyrolysis conditions are as follows: in an argon atmosphere, first heat to 180 °C, keep warm for 1.5 h, then heat to 350 °C, keep warm for 2.5 h, and finally heat to 1000 °C, keep warm for 2 h, and the heating rate is 1 °C / min.

[0052] Embodiment 4:

[0053] A method for preparing a PDC-doped liquid metal composite material comprises the following steps:

[0054] (1) 0.3 g of Galinstan and 50 mL of 4 mmol / L KMnO4 were added to a cell disruptor. The power of the cell disruptor was adjusted to 1400 W. The mixed solution was ultrasonicated for 30 min in an ice bath. After the ultrasonication, the mixed solution was washed with water and tetrahydrofuran for 3 times, respectively. When washing with water, the centrifuge speed was 2500 rpm for 3 min. When washing with tetrahydrofuran, the centrifuge speed was 1500 rpm for 3 min. MnO2@Galinstan with a core-shell structure was obtained.

[0055] (2) The MnO2@Galinstan obtained in step (1) is dissolved in tetrahydrofuran, and then doped with PDC, with the doping amount of MnO2@Galinstan being 0.5%. After being evenly mixed, the tetrahydrofuran is removed by rotary evaporation, and the PDC-doped liquid metal composite material is obtained by curing and high-temperature pyrolysis; the curing condition is a light irradiation intensity of 15 mW / cm 2 The high temperature pyrolysis conditions are as follows: in an argon atmosphere, first heat to 180 °C, keep warm for 1.5 h, then heat to 350 °C, keep warm for 2.5 h, and finally heat to 1000 °C, keep warm for 2 h, and the heating rate is 1 °C / min.

[0056] Embodiment 5:

[0057] A method for preparing a PDC-doped liquid metal composite material comprises the following steps:

[0058] (1) 0.3 g EGaln and 50 mL 4 mmol / L KMnO4 were added to a cell disruptor, and the power of the cell disruptor was adjusted to 1400 W. The mixed solution was ultrasonicated for 30 min in an ice bath. After the ultrasonication, the mixed solution was washed with water and tetrahydrofuran for 3 times, respectively. When washing with water, the centrifuge speed was 2500 rpm for 3 min. When washing with tetrahydrofuran, the centrifuge speed was 1500 rpm for 3 min. MnO2@EGaln with a core-shell structure was obtained.

[0059] (2) The MnO2@EGaln obtained in step (1) is dissolved in tetrahydrofuran, and then doped with PDC, the doping amount of MnO2@EGaln is 0.25%, and after being evenly mixed, the tetrahydrofuran is removed by rotary evaporation, and the PDC-doped liquid metal composite material is obtained by curing and high-temperature pyrolysis; the curing condition is a light irradiation intensity of 15 mW / cm 2 The high temperature pyrolysis conditions are as follows: in an argon atmosphere, first heat to 180 °C, keep warm for 1.5 h, then heat to 350 °C, keep warm for 2.5 h, and finally heat to 1000 °C, keep warm for 2 h, and the heating rate is 1 °C / min.

[0060] Embodiment 6:

[0061] A method for preparing a PDC-doped liquid metal composite material comprises the following steps:

[0062] (1) 0.3 g EGaln and 50 mL 4 mmol / L KMnO4 were added to a cell disruptor, and the power of the cell disruptor was adjusted to 1400 W. The mixed solution was ultrasonicated for 30 min in an ice bath. After the ultrasonication, the mixed solution was washed with water and tetrahydrofuran for 3 times, respectively. When washing with water, the centrifuge speed was 2500 rpm for 3 min. When washing with tetrahydrofuran, the centrifuge speed was 1500 rpm for 3 min. MnO2@EGaln with a core-shell structure was obtained.

[0063] (2) The MnO2@EGaln obtained in step (1) is dissolved in tetrahydrofuran, and then doped with PDC, the doping amount of MnO2@EGaln is 0.75%, and after being evenly mixed, the tetrahydrofuran is removed by rotary evaporation, and the PDC-doped liquid metal composite material is obtained by curing and high-temperature pyrolysis; the curing condition is a light irradiation intensity of 15 mW / cm 2The high temperature pyrolysis conditions are as follows: in an argon atmosphere, first heat to 180 °C, keep warm for 1.5 h, then heat to 350 °C, keep warm for 2.5 h, and finally heat to 1000 °C, keep warm for 2 h, and the heating rate is 1 °C / min.

[0064] Embodiment 7:

[0065] A method for preparing a PDC-doped liquid metal composite material comprises the following steps:

[0066] (1) 0.3 g EGaln and 50 mL 4 mmol / L KMnO4 were added to a cell disruptor, and the power of the cell disruptor was adjusted to 1400 W. The mixed solution was ultrasonicated for 30 min in an ice bath. After the ultrasonication, the mixed solution was washed with water and tetrahydrofuran for 3 times, respectively. When washing with water, the centrifuge speed was 2500 rpm for 3 min. When washing with tetrahydrofuran, the centrifuge speed was 1500 rpm for 3 min. MnO2@EGaln with a core-shell structure was obtained.

[0067] (2) dissolving the MnO2@EGaln obtained in step (1) in tetrahydrofuran, and then doping it with PDC, wherein the mass ratio of MnO2@EGaln to PDC is 1%, and after being evenly mixed, removing the tetrahydrofuran by rotary evaporation, and obtaining a PDC-doped liquid metal composite material by curing and high-temperature pyrolysis; the curing condition is a light irradiation intensity of 15 mW / cm 2 The high temperature pyrolysis conditions are as follows: in an argon atmosphere, first heat to 180 °C, keep warm for 1.5 h, then heat to 350 °C, keep warm for 2.5 h, and finally heat to 1000 °C, keep warm for 2 h, and the heating rate is 1 °C / min.

[0068] Experimental Example 1: Performance Characterization of Metal Oxide@Gallium-based Liquid Metal Composite Materials

[0069] The MnO2@EGaln prepared in Example 1 was characterized. The micromorphology and elemental analysis of the composite material were carried out by field emission scanning electron microscopy (SEM, Medel 1530, LEO, Germany), and the microcrystalline structure of the sample was analyzed by X-ray diffractometer (XRD, SmartLab SE, Rigaku, Japan).

[0070] The microscopic morphology characterization results are as follows Figure 1 As shown in Figure 2, it can be seen that the prepared composite material has a typical core-shell structure. The elemental analysis results are shown in Figure 2. Figure 2 As shown in the figure, it can be seen that the composite material sample contains Mn, Ga and In elements. The microscopic crystal structure analysis results are shown in Figure 3As shown, it can be seen that the composite material sample includes characteristic peaks of MnO2 crystallization and EGaln crystallization. The results show that the present invention successfully prepared the metal oxide@gallium-based liquid metal composite material MnO2@EGaln.

[0071] Experimental Example 2: Photocuring performance and elemental analysis characterization of PDC-doped liquid metal composites

[0072] The samples of the PDC-doped liquid metal composite materials obtained in Example 1 and Examples 5-7 after curing were characterized. The samples were subjected to the same irradiation time (6 s) and irradiation intensity (15 mW / cm 2 )’s light curing performance test.

[0073] Test results such as Figure 4 and Figure 5 As shown in the figure, it can be seen that the surface quality of the precision sample decreases slightly with the increase of MnO2@EGaln doping amount, but the curing accuracy does not decrease significantly. The thickness of the cured layer decreases with the increase of MnO2@EGaln doping amount ( Figure 5 ), but all are larger than 200μm, meeting the printing conditions.

[0074] The samples obtained in Example 1 and Example 7 were printed using a DLP 3D printer and then pyrolyzed at 1000°C. The comparison between the printed blank and the pyrolyzed sample is shown in FIG. Figure 6 As shown in the figure, it can be seen that the pyrolysis composite material sample has no defects and deformation, and the shrinkage of the sample during the pyrolysis process is linear shrinkage.

[0075] The element distribution analysis of the sample after 3D printing pyrolysis in Example 1 was performed using a transmission electron microscope (TEM, FEI Talos F200X, FEI, USA). The experimental results are as follows: Figure 7 As shown, it can be seen that the sample contains Ga, In, Mn, C, B, O and Si elements, and each element is evenly distributed.

[0076] Test Example 3: Dielectric and Absorption Performance Analysis and Characterization

[0077] A standard annular sample (φ7.03×3.04×2.50 mm) was prepared by 3D printing and pyrolysis at 1000°C (high temperature pyrolysis conditions are the same as those in Example 1). The complex dielectric constant of the sample was tested in the frequency range of 2-18 GHz by a vector network analyzer (VNA, MS4644A, Anritsu, Japan) using a coaxial method. The complex dielectric constant of the sample in Example 1 is as follows: Figure 8 As shown, the real part of the complex dielectric constant is 10.29~4.87, and the imaginary part is 3.01~4.84. The reflection coefficient of the composite material with different thicknesses in the frequency range of 2-18GHz is further calculated, as shown in Fig. 9As shown, it can be seen that when the sample thickness is 2.4 mm, the effective absorption bandwidth EAB (RL≤-10) is 7.17 GHz and the minimum reflection coefficient RL is -53.59.

[0078] The sample prepared in Example 7 was tested and analyzed in the same manner, and the complex dielectric constant was measured as follows: Fig.10 As shown in the figure, the real part of the complex dielectric constant is 14.93~6.89, and the imaginary part is 4.25~5.88. It can be seen that the increase in the amount of MnO2@EGaln effectively increases the real and imaginary parts of the dielectric constant of the composite material. The reflection coefficient of the composite material at different thicknesses in the frequency range of 2-18GHz is further calculated, as shown in Fig.11 As shown, it can be seen that when the sample thickness is 1.9 mm, the effective absorption bandwidth EAB (RL≤-10) is 5.21 GHz and the minimum reflection coefficient RL is -37.18.

[0079] A standard annular sample (φ7.03×3.04×2.50 mm) was prepared by 3D printing and pyrolysis at 900°C (high temperature pyrolysis conditions are the same as in Example 1). The complex dielectric constant of the sample in Example 1 is as follows: Fig.12 As shown in the figure, the real part of the complex dielectric constant is 12.98~6.80, and the imaginary part is 5.14~2.72. It can be seen that when the MnO2@EGaln doping amount remains unchanged, the dielectric constant of the composite material can be regulated by adjusting the pyrolysis temperature. The reflection coefficient of the composite material with different thicknesses in the frequency range of 2-18GHz is further calculated, as shown in Fig.13 As shown, it can be seen that when the sample thickness is 1.9 mm, the effective absorption bandwidth EAB (RL≤-10) is 5.12 GHz and the minimum reflection coefficient RL is -37.59.

[0080] The same method was used to prepare a standard annular sample (φ7.03×3.04×2.50 mm) using the ceramic precursor in Example 1 as a raw material for 3D printing and pyrolysis at 1000°C (high temperature pyrolysis conditions were the same as in Example 1). The complex dielectric constant was measured as follows: Fig.14 As shown in FIG. 1 , the real part of the complex dielectric constant is 5.71 to 3.94, and the imaginary part is 1.81 to 0.80. The dielectric constant is relatively low, significantly inferior to the sample prepared in the embodiment of the present invention. The reflection coefficient of the composite material with different thicknesses in the frequency range of 2-18 GHz is further calculated, as shown in FIG. Fig.15 As shown, it can be seen that when the sample thickness is 3.4 mm, the effective absorption bandwidth EAB (RL≤-10) reaches the maximum, but it is only 1.52 GHz, and the minimum reflection coefficient RL is -11.34. In summary, it can be seen that the pure PDC obtained by pyrolysis at 1000 ° C has almost no absorption performance.

[0081] In summary, the present invention can achieve a large range of regulation of the dielectric properties and absorbing properties of the composite material by doping a small amount of core-shell structured metal oxide@gallium-based liquid metal material into PDC, and will not affect the intrinsic properties of the PDC matrix such as the photocuring performance. It has excellent dielectric constant and absorbing performance regulation capabilities and has potential application value in the field of high-performance absorbing material preparation.

[0082] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a PDC-doped liquid metal composite material, characterized in that: The following steps are involved: (1) mixing a gallium-based liquid metal and a metal oxide solution, washing, and obtaining a metal oxide@gallium-based liquid metal composite material; (2) dissolving the metal oxide@gallium-based liquid metal composite material obtained in step (1) in a solvent, adding a ceramic precursor and mixing evenly, removing the solvent, and curing and high-temperature pyrolysis to obtain a composite material.

2. The method for preparing the PDC-doped liquid metal composite material according to claim 1, characterized in that: In the step (1), the mass volume ratio of the gallium-based liquid metal to the metal oxide solution is 0.1-0.5 g: 20-100 mL; the gallium-based liquid metal is EGa1n, Ga or Galinstan, and the metal oxide solution is KMnO4 solution.

3. The method for preparing the PDC-doped liquid metal composite material according to claim 2, characterized in that: The concentration of the metal oxide solution is 2-10 mmol / L.

4. The method for preparing the PDC-doped liquid metal composite material according to claim 1, characterized in that: The mixing conditions in step (1) are: ultrasound at 1200-1600W for 20-40min in an ice bath.

5. The method for preparing the PDC-doped liquid metal composite material according to claim 1, characterized in that: The washing in step (1) is washing with water and tetrahydrofuran in sequence.

6. The method for preparing the PDC-doped liquid metal composite material according to claim 1, characterized in that: In the step (2), the mass ratio of the metal oxide@gallium-based liquid metal composite material to the ceramic precursor is: 0.1%-2%:1; and the solvent is tetrahydrofuran.

7. The method for preparing the PDC-doped liquid metal composite material according to claim 1, characterized in that: The curing condition in step (2) is a light irradiation intensity of 10-20 mW / cm 2 , time is 1-30s.

8. The method for preparing the PDC-doped liquid metal composite material according to claim 1, characterized in that: The conditions for high-temperature pyrolysis in step (2) are: in a rare gas atmosphere, first heating to 150-200°C, keeping warm for 1-2 hours, then heating to 300-400°C, keeping warm for 2-3 hours, and finally heating to 900-1200°C, keeping warm for 2-3 hours, with a heating rate of 1-2°C / min.

9. A PDC-doped liquid metal composite material, characterized in that: The method is prepared by the method according to any one of claims 1 to 8.

10. Use of the PDC-doped liquid metal composite material according to claim 9 in the preparation of wave absorbing materials.